1998
DOI: 10.1046/j.1525-1497.1998.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in men with erectile dysfunction

Abstract: OBJECTIVE:To assess health-related quality of life (HRQOL) in men with erectile dysfunction. DESIGN:Descriptive survey with general and disease-specific measures. The instrument contained three established, validated HRQOL measures, a validated comorbidity checklist, and sociodemographics. The RAND 36-Item Health Survey 1.0 (SF-36) was used to assess general HRQOL. Sexual function and sexual bother were assessed using the UCLA Prostate Cancer Index. The marital interaction scale from the Cancer Rehabilitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
213
0
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(233 citation statements)
references
References 33 publications
(33 reference statements)
11
213
0
7
Order By: Relevance
“…34 Recognition of sexual dysfunction may be a powerful motivator for lifestyle change in middle-aged and older men. Moreover, both ED 35 and LUTS 36 are associated with increased cardiovascular risk, adversely affect quality of life and mood and interfere with interpersonal relationships, often necessitating medication or surgery. In contrast, we have shown that a simple lifestyle intervention is effective in improving sexual and urinary dysfunction in obese men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Recognition of sexual dysfunction may be a powerful motivator for lifestyle change in middle-aged and older men. Moreover, both ED 35 and LUTS 36 are associated with increased cardiovascular risk, adversely affect quality of life and mood and interfere with interpersonal relationships, often necessitating medication or surgery. In contrast, we have shown that a simple lifestyle intervention is effective in improving sexual and urinary dysfunction in obese men.…”
Section: Discussionmentioning
confidence: 99%
“…The International Prostate Symptom Scale (IPSS) is a series of questions used to assess the severity of irritative (frequency, urgency, nocturia) and obstructive LUTSs (incomplete emptying, intermittency, weak stream, straining), attributable to bladder outlet obstruction caused by prostatic enlargement. 19 Symptoms are classified as mild (score 0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) or severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Questionnairesmentioning
confidence: 99%
“…29 The SF-36 has been used extensively in research on men with prostate carcinoma and quality of life as well as in research on men seeking help for ED, 30 allowing us to compare our survey sample with similar cohorts of men. We predicted that men with better perceived physical and mental health also would have better sexual outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…35 Our sample's scores also were similar to norms established in other large registries for patients with prostate carcinoma on the SF-36 and the UCLA PCI urinary and bowel function scales. 28,30 …”
Section: Sexual Outcomesmentioning
confidence: 99%
“…En un estudio realizado en un grupo de pacientes en hemodiá lisis, el dominio emocional del cuestionario SF-36 está muy asociado con la DE independientemente de otras comorbilidades 15 . Cabe destacar que aunque en algú n caso se ha descrito una asociació n predominante de la DE con los dominios físicos de la calidad de vida, reflejada por el cuestionario MOS-SF36 16 , se afectan preferentemente los dominios emocionales 17 .…”
Section: Discusió Nunclassified